2018
DOI: 10.1016/j.ijrobp.2018.07.1020
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Depth of Invasion vs Tumor Thickness in Determining Risk of Nodal Disease in Early Oral Tongue Squamous Cell Carcinoma

Abstract: For 20 cases, deep-learning delineation outperformed 4 of the 8 radiation oncologists, with mean DSC of 0.766 against 0.691, 0.699, 0.704 and 0.719 (all P < 0.05); while performed comparably to another 4 oncologists. With the assistance of deep-learning delineation, increased delineation accuracy was observed in 5 oncologists (mean DSC increased from 0.731 to 0.779; all P < 0.05) and stable DSC in 3 oncologists. Furthermore, decreased multi-observer DSC was observed (0.774 AE 0.0773 vs. 0.702 AE 0.114; P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The difference was less than 1 mm in 21.2% [17]. Similarly, 53% of cases in a study by Liu et al had identical TT and DOI or a difference less than 1 mm [18]. Our review shows the difference between the mean DOI and TT to be 1.4 mm and median DOI and TT to be 1 mm.…”
Section: Stage Revision Based On Doi and Its Prognostic Significancesupporting
confidence: 60%
“…The difference was less than 1 mm in 21.2% [17]. Similarly, 53% of cases in a study by Liu et al had identical TT and DOI or a difference less than 1 mm [18]. Our review shows the difference between the mean DOI and TT to be 1.4 mm and median DOI and TT to be 1 mm.…”
Section: Stage Revision Based On Doi and Its Prognostic Significancesupporting
confidence: 60%
“…However, there were two notable shortcomings with the coding of tumor thickness/depth of invasion in this NCDB analysis. First, these two distinct pathologic features were coded as a single variable, which is problematic because of their differing numerical thresholds for predicting regional nodal metastasis 22 . Second, nearly half (48%) had missing data.…”
Section: Discussionmentioning
confidence: 99%
“…First, these two distinct pathologic features were coded as a single variable, which is problematic because of their differing numerical thresholds for predicting regional nodal metastasis. 22 Second, nearly half (48%) had missing data. A literature review and meta-analysis identified tumor thickness and depth of invasion as important prognostic factors for oral cavity cancers, although primary tumors involving the thin mucosal layer of the alveolar ridge were not included in these publications.…”
Section: Discussionmentioning
confidence: 99%